2022
DOI: 10.4069/kjwhn.2022.02.03.1
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of depression in pregnant women in Korea based on the 2019 Korean Community Health Survey: a cross-sectional study

Abstract: Purpose: Various individual and social factors influence depression in pregnant women. The purpose of this study was to identify the influence of socioeconomic status, health behaviors, and health status on depression of pregnant women in Korea. Methods: This study analyzed data from the 2019 Korean Community Health Survey conducted from August to October 2019. The data of 1,096 pregnant women between the ages of 19 and 55 years were analyzed using descriptive statistics, independent-test and chi-square tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Suggestively, a lower level of education may have a role in both depressive and weight-gain outcomes. For instance, Kim et al [34] reported that the mean score of depression measured with the Patient Health Questionnaire-9 (PHQ-9) [35] during pregnancy was associated with low education level as well as decreased with subjective health status (all p < 0.001). Conversely, Banite et al [36] have shown that employed women presented a lower level of PD whereas a higher level of education was positively associated with a higher risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestively, a lower level of education may have a role in both depressive and weight-gain outcomes. For instance, Kim et al [34] reported that the mean score of depression measured with the Patient Health Questionnaire-9 (PHQ-9) [35] during pregnancy was associated with low education level as well as decreased with subjective health status (all p < 0.001). Conversely, Banite et al [36] have shown that employed women presented a lower level of PD whereas a higher level of education was positively associated with a higher risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Improving behaviors related to pregnancy healthcare can serve as an effective strategy for reducing prenatal depression. The frequency of breakfast consumption, sleep duration, and drinking habits all have an impact on prenatal depression; thus, a diet rich in vitamins and increased physical activity are recommended during pregnancy [9]. Even amidst a pandemic, participating in online fitness classes can increase physical activity levels, thereby bolstering pregnant women's resilience against prenatal depression.…”
Section: Introductionmentioning
confidence: 99%